Negotiating Qur’anic Authority in the Algorithmic Age: Young Marriage Narratives on TikTok - Hayati, Saropa Nor; Nafiza, Azka Zahro (Suhuf: International Journal of Islamic Studies, 2026)
Background: This study discusses narratives of early marriage legitimized by religious narratives constructed, mediated, and debated in the digital spaces through TikTok accounts @azkiavee the extent to which these narratives are in accordance with the principles of the Qur'an. Objective: This study aims to analyze the construction of meaning related to early marriage on TikTok and evaluate it through the normative framework of the Qur'an, particularly the concept of rusyd. Methodology: Using Kozinets' qualitative netnography, this study analyzes the top 100 comments and uses Nick Couldry & Andreas Hepp's theory of Mediated Construction of Reality. Results: The findings reveal three dominant categories of meaning: Qur'anic resistance, religious legitimization, and normalization of early marriage, which describe the dynamic negotiation of religious authority in a mediated context. Conclusion: Islamic marriage ethics demand comprehensive intellectual, emotional, and moral maturity beyond biological age, and social media plays a role in shaping and producing these meanings. This study identifies a significant gap in the existing academic literature, where discussions of young marriage are presented descriptively without critiquing theological simplifications in digital media.